The problems of THE immunogenicity of biologicals: theory and practice - D E Karateyev (Современная ревматология)
The variously faceted and clinically important problem of immunogenicity of recombinant biologicals that have become an integral part of therapy for inflammatory rheumatic diseases is considered.